Islamic Religious Education in the Construction of a Multicultural Society: Negotiating Theological Exclusivity and Social Inclusivity - Selvia Yolanda; Mahmud Arif (Journal of Education and Teacher Training Innovation, 2026)
The increasing intensity of social interaction in multicultural societies has intensified encounters between theological truth claims and demands for social openness, which, within Islamic religiosity grounded in Islamic creed (ʿaqīdah), is often perceived as a conceptual tension. This study aims to identify the ideal pattern of the relationship between theological exclusivity and social inclusivity from the perspective of Islamic religiosity grounded in Islamic creed (ʿaqīdah) and to examine its implications for Islamic Religious Education (IRE), as well as to explain its relevance to strengthening religious moderation in multicultural societies. This qualitative study takes the form of a literature review using a descriptive analytical approach. Data were obtained through documentation by examining normative Islamic sources as well as various scholarly literature relevant to the subject matter. The findings of this study show that theological exclusivity constitutes the epistemic dimension of Islamic religiosity, affirming commitment to revealed truth and preserving religious identity, while social inclusivity functions as an ethical orientation that enables just, balanced, and harmonious engagement with diversity. The apparent tension between the two does not stem from their substantive nature, but rather from a reductionist understanding that fails to distinguish between theological and social domains. Within a proportional framework, these dimensions are not mutually exclusive but mutually reinforcing. Furthermore, Islamic Religious Education serves as a strategic medium for integrating firm theological commitment with inclusive social values, enabling Muslims to engage constructively with multicultural realities without compromising the integrity of faith. The contribution of this study confirms that religious moderation can be strengthened through a clear conceptual distinction between belief and social relations, allowing both to operate within their respective domains without contradiction. In addition, this study contributes to the development of a conceptual framework for Islamic Religious Education that balances theological exclusivity and social inclusivity in multicultural societies.